Xp pseudoautosomal gene haploinsufficiency and linear growth deficiency in three girls with chromosome Xp22;Yq11 translocation. Issue 11 (November 1996) - Joseph, M; Cantú, E S; Pai, G S; Willi, S M; Papenhausen, P R; Weiss, L
Abstract : Colony stimulating factor-2 receptor alpha (CSF2RA) and interleukin-3 receptor alpha (IL3RA), two genes from the chromosome Xp and Yp pseudoautosomal region (PAR), have been suggested as candidate genes for short stature in Turner syndrome. We report three girls with X;Y translocation (46, X, der(X)t(X;Y)(p22;q11) initially detected by amniocentesis. The terminal portion of the X chromosome distal to the translocation breakpoint at Xp22 was deleted on the derivative X chromosome in all three patients. Each had normal stature at birth, with greater than expected deceleration of growth velocity by the second year. Using fluorescence in situ hybridisation (FISH), we have shown deletion of the CSF2RA and IL3RA loci on the derivative X chromosomes of all three patients. The role of CSF2RA and IL3RA haploinsufficiency in linear growth and final adult stature is discussed. Additional studies, particularly of molecular deletions within the PAR, are needed to improve our understanding of the role of these and other PAR loci in the genetic control of adult stature.